Uniformly convex subspaces of measures with the kantorovich norm - Kukharchuk, I.A. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2023)
In this paper, we consider signed Borel measures on a compact metric space. We study the uniform convexity of the Kantorovich norm on subspaces of the whole space of signed measures. We construct an example of an infinite-dimensional subspace of measures on which the Kantorovich norm is uniformly convex. We also obtain an example of an infinite compact set $(X, ρ)$ such that all uniformly convex subspaces of the space of measures on $X$ are finite-dimensional.